Konversi Batubara Menjadi Syngas Menggunakan Metode Gasifikasi Dengan Variasi Air Fuel Ratio (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
Coal is one of the natural resource commodities produced from mining activities in Indonesia and is a strategic mining material in the supply of energy sources. Especially for Banten , coal were found in South Banten Bayah. Gasification is a solution for the use of coal. Coal gasification is the process of converting solid coal into a gas mixture. The main reactions that occur are the water gas, boundouard and water gas-shift reactions. This study aims to determine the effect of Air Fuel Ratio (AFR) gasifications in the Banten Bayah Natural coal gasification process which produces synthesis gas with an H2/Co Ratio 2. The measured parameters are the composition of H2 and CO gases using Gas Chromatography. The gasification process is carried out with an updraft fixed bed reactor using steam medium on a 14 mesh coal size of 300 grams with AFR variations of 1.5, 2 and 2.5 with temperature 800oC. The activation energy of the gasification reaction can be reduced by using Ca(OH)2 catalysts as much as 3% of the mass of coal. From the research results obtained the best H2/CO ratio syngas gas composition at AFR 1.5 temperature 800oC using Ca(OH)2 catalyst which is 1.98 with H2 gas composition 33.8% and CO gas 17.1%..